A Homozygous Nme7 Mutation Is Associated with Situs Inversus Totalis. Issue 8 (9th May 2016) - Reish, Orit; Aspit, Liam; Zouella, Arielle; Roth, Yehudah; Polak‐Charcon, Sylvie; Baboushkin, Tatiana; Benyamini, Lilach; Scheetz, Todd E.; Mussaffi, Huda; Sheffield, Val C.; Parvari, Ruti
Abstract : Situs inversus totalis defines randomized internal organ laterality instead of the normal left to right asymmetry. Using homozygosity mapping and exome sequencing, supported by expression in normal human tissues, we detected for the first time the causative gene‐ NME7 ‐ to pattern the embryonal right to left asymmetry. The mutation we detected disrupts the NME7 protein in a critical domain NDK2 necessary for its interaction with other proteins involved in the signaling required for the normal asymmetric laterality. ABSTRACT: We investigated the cause of situs inversus totalis (SIT) in two siblings from a consanguineous family. Genotyping and whole‐exome analysis revealed a homozygous change in NME7, resulting in deletion of an exon causing an in‐frame deletion of 34 amino acids located in the second NDK domain of the protein and segregated with the defective lateralization in the family. NME7 is an important developmental gene, and NME7 protein is a component of the γ‐tubulin ring complex. This mutation is predicted to affect the interaction of NME7 protein with this complex as it deletes the amino acids crucial for the binding. SIT associated with homozygous deletion in our patients is in line with Nme7 −/‐ mutant mice phenotypes consisting of congenital hydrocephalus and SIT, indicating a novel human laterality patterning role for NME7. Further cases are required to elaborate the full human phenotype associated with NME7 mutations.